"Childrens are not just "little adults". The rate of medication related problems and its predictors among patients admitted to pediatric ward of southwestern Ethiopian hospital: A prospective observational study. (October 2021) - Bekele, Firomsa; Bereda, Gudisa; Tamirat, Lalisa; Geleta, Bonsa Amsalu; Jabessa, Dabala
Abstract: Background: The rate of medication related problems is high in developing countries due to the complexity of pediatrics medication management. Pediatric population should have their own dosage regimens. The pediatric dosage regimens were derived from the adult dose that might lead to sudden reach of sub or supra-therapeutic doses. As the result, the medication therapy management is difficult in this populations. Despite this, a scanty of studies were conducted on medication related problems among pediatric populations. Therefore, this study examined the prevalence and risk factors for the occurrence of the medication related problems among patients admitted to pediatric ward of Mettu karl referral hospital. Patients and methods: The pediatric population who were received the pharmacotherapy for their disease was observed and followed for the occurrences of medication related problems at pediatric wards of Mettu karl referral hospital from February 12, 2020 to February 24, 2021. Patients whose age was less than or equal to 18 years and who were on drug therapy or who needs drug therapy during study period were included. The possibility of adverse drug reactions developed from the drug was assessed by using the Naranjo scale. Multivariable logistic regression analysis was used to determine the predictors of medication related problems. Result: Over the study period, a total of 189 pediatric populations were included. Among these, 115 (60.8%) were males, and the mean age of the patients was 1.4339 ± 0.864 years. The mediciation related problems was found among 121(64.01%) of pediatric patients. Among seven types of drug therapy problems unnecessary drug therapy, need additional drug therapy, ineffective drug therapy and dose too high were the most predominantly occured DRP that accounted 74 (27.72%), 67 (25.09%), 43 (16.10%), 36 (13.48%), respectively. The mean number of hospital stay was 4.29 days with minimum and maximum stay of 2 and 9 days and antibiotics 364(51.3%) were the most common class of drugs that was associated with drug related problems. Being a neonate (AOR = 1.48, 95CI%: 1.69–7.42, P = <0.001), hospital stay greater than or equal to seven days (AOR = 1.98, 95CI%: 2.471–12.644, P = 0.016), and the presence of co-morbidity(AOR = 2.507, 95CI%: 3.270–4.949, P = 0.080) were the predictors of the medication related problems. Conclusion: The prevalence of medication-related problems in pediatrics patient was found to be high. Being neonatal, prolonged hospital stay and the presence of a multiple disease were the predictors of medication-related problems in pediatric patients. Therefore special attention should be given for newborns, prolonged hospital stay and patients having co-morbidity. Besides this, the drug information service and the patients round activity should be started by clinical pharmacist to decrease the occurences of any preventable medication related problems. Highlights: DRP is the problem that interferes with a patient's pharmacotherapy that results in poor treatment outcomes. The rate of medication related problems in developing countries is high. " Children are not just "little adults" in which they should have their own pharmacokinetic and pharmacodynamics profile.